High-throughput ultra-sensitive discrimination of single nucleotide polymorphism via click chemical ligation. Issue 1 (14th November 2019) - Zhou, Qian-Yu; Zhong, Xin-Ying; Zhao, Ling-Li; Wang, Li-Juan; Zhou, Ying-Lin; Zhang, Xin-Xiang
Abstract : CuAAC-based ligation-assisted assays: the CuAAC chemical ligation reaction for SNP detection. Abstract : Single nucleotide polymorphisms (SNPs) have been proven to be important biomarkers for disease diagnosis, prognosis and disease pathogenesis. Here, taking the advantages of a self-assembled oligonucleotide sandwich structure and robust chemical reactions, we have developed a simple, high-throughput and effective colorimetric analytical technique termed CuAAC-based ligation-assisted assays (CuAAC-LA) for SNP detection using a DNA-BIND 96-well plate. With the 5′-azide and 3′-alkyne groups labelled on two oligonucleotide probes, the target DNA can direct a Cu(i )-catalyzed alkyne–azide cycloaddition (CuAAC) click reaction. Since the small difference in duplex stability caused by a single-nucleotide mismatch was amplified by the steric effects of these reactive groups for the ligation reaction of an unstable duplex, CuAAC-LA exhibited an ultra-sensitive discrimination ability for a mutant type target in the presence of large amounts of wild type targets. As low as 0.05% SNP could be clearly detected, which was better than most previously reported methods by various DNA ligases, indicating that a simple and rapid synthetic method i.e., the DNA template-directed click reaction held the potential to replace the ligase for SNP detection.